ENHANCING CREATIVITY IN ORNAMENTAL ART THROUGH GROUP WORK AND COLLABORATIVE METHODS - Aslonova Navro‘za Hoshim qizi, (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: Group work and collaborative methods play a crucial role in fostering creativity in ornamental art education. This article analyzes how students’ creative potential can be enhanced through cooperative activities, joint problem-solving, and collaborative design projects. By engaging in group work, students develop aesthetic decision-making skills, critical thinking, and the ability to harmonize composition and color schemes. Collaborative methods encourage active participation, peer feedback, and the exchange of ideas, which collectively contribute to improving students’ artistic competencies and creative confidence. The study highlights effective strategies for implementing collaborative techniques in the classroom to maximize students’ creative development.